Positive outcome of a twin pregnancy after the administration of tocilizumab to a pregnant woman with severe COVID-19 - Dickov Isidora; Bulatović Sanja; Petrović Đorđe; Antić-Trifunović Ksenija; Krsman Anita (Srpski Arhiv za Celokupno Lekarstvo, 2024)
Introduction. Tocilizumab is an IgG1 monoclonal antibody targeting the interleukin 6 receptor. We present a case of a pregnant woman with COVID-19 pneumonia, which rapidly worsened despite the advanced treatment. Therefore, the administration of tocilizumab was deemed necessary. Case outline. Our patient was a 31-year-old pregnant woman hospitalized on the seventh day after contracting COVID-19. She was in the 21st week of a twin pregnancy, specifically monochorionic diamniotic. Her general condition was severe, accompanied by elevated inflammation markers: C-reactive protein – 94.6 (mg/L), procalcitonin – 1.44 (ng/mL), and IL-6 – 79.3 (pg/mL), along with extensive bilateral pneumonia evident in the X-ray image. She required respiratory support in the form of high flow nasal cannula, continuous positive airway pressure, and intensive monitoring. The following day, her condition deteriorated further, prompting the decision to administer tocilizumab. After receiving tocilizumab, the X-ray image deteriorated, but the inflammation markers decreased. After 33 days of hospitalization, she was discharged with normal laboratory findings and a clear X-ray. On July 16, the patient was admitted to the Clinic for Gynecology and Obstetrics of the Clinical Center of Vojvodina at 36 weeks of gestation (35 gw + 2 day) due to premature contractions. On the same day, a caesarean section was performed, and both neonates were in good general condition. Conclusion. Managing severe COVID-19 in pregnant women poses significant challenges. This case study suggests that tocilizumab may hold efficacy in treating this condition.